Minor stroke in large vessel occlusion: A matched analysis of patients from the German Stroke Registry–Endovascular Treatment (GSR‐ET) and patients from the Safe Implementation of Treatments in Stroke–International Stroke Thrombolysis Register (SITS‐ISTR). (19th February 2022) - Feil, Katharina; Matusevicius, Marius; Herzberg, Moriz; Tiedt, Steffen; Küpper, Clemens; Wischmann, Johannes; Schönecker, Sonja; Mengel, Annerose; Sartor‐Pfeiffer, Jennifer; Berger, Katharina; Dimitriadis, Konstantin; Liebig, Thomas; et al.
Abstract: Background and purpose: Reperfusion treatment in patients presenting with large vessel occlusion (LVO) and minor neurological deficits is still a matter of debate. We aimed to compare minor stroke patients treated with endovascular thrombectomy (EVT) and intravenous thrombolysis (IVT) or IVT alone. Methods: Patients enrolled in the German Stroke Registry–Endovascular Treatment (GSR‐ET) and the Safe Implementation of Treatments in Stroke–International Stroke Thrombolysis Registry (SITS‐ISTR) between June 2015 and December 2019 were analyzed. Minor stroke was defined as National Institutes of Health Stroke Scale (NIHSS) score ≤5, and LVO as occlusion of the internal carotid, carotid‐T, middle cerebral, basilar, vertebral or posterior cerebral arteries. GSR‐ET and SITS‐ISTR IVT‐treated patients were matched in a 1:1 ratio using propensity‐score (PS) matching. The primary outcome was good functional outcome at 3 months (modified Rankin Scale score 0–2). Results: A total of 272 GSR‐ET patients treated with EVT and IVT (age 68.6 ± 14.0 years, 43.4% female, NIHSS score 4 [interquartile range 2–5]) were compared to 272 IVT‐treated SITS‐ISTR patients (age 69.4 ± 13.7, 43.4% female, NIHSS score 4 [2–5]). Good functional outcome was seen in 77.0% versus 82.9% ( p = 0.119), mortality in 5.9% versus 7.9% ( p = 0.413), and intracranial hemorrhage in 8.8% versus 12.5% ( p = 0.308) of patients in the GSR‐ET versus the SITS‐ISTR IVT group, respectively. In a second PS‐matched analysis, 624 GSR‐ET patients (IVT rate 56.7%) and 624 SITS‐ISTR patients (IVT rate 100%), good outcome was more often observed in the SITS‐ISTR patients (68.2% vs. 80.9%; p < 0.001), and IVT independently predicted good outcome (odds ratio 2.16, 95% confidence interval 1.43–3.28). Conclusions: Our study suggests similar effectiveness of IVT alone compared to EVT with or without IVT in minor stroke patients. There is an urgent need for randomized controlled trials on this topic. Abstract : Figure 2 The benefit of endovascular thrombectomy (EVT) treatment for minor stroke patients (NIHSS ≤5) is still unknown. We matched German Stroke Registry–Endovascular Treatment (GSR‐ET) patients treated with EVT, with or without intravenous thrombolysis (IVT) treatment, to Safe Implementation of Treatments in Stroke –International Stroke Thrombolysis Register (SITS‐ISTR) patients treated with IVT alone. Our observational results suggest that the efficacy is similar between treatment options, and EVT appears to be safe for this patient group.